PAI-1 secretion of endometrial and endometriotic cells is Smad2/3- and ERK1/2-dependent and influences cell adhesion - Sui, Cong; Mecha, Ezekiel; Omwandho, Charles O. A.; Starzinski-Powitz, Anna; Stammler, Angelika; Tinneberg, Hans-Rudolf; Konrad, Lutz; Justus Liebig University Giessen (My University, 2016)
In the endometrium transforming growth factor-betas (TGF-ßs) are involved mainly in menstruation and endometriosis. After binding of the ligands to the high-affinity receptors, TGF-ß receptors (TBR1 and TBR2), TGF-ßs activate Smad signaling to modulate gene expression and cellular functions. However, recently also Smad-independent pathways have been studied in more details. To evaluate both pathways, we have analyzed TGF-ß signaling in human endometrial and endometriotic cells. Although endometrial and endometriotic cells secrete TGF-ß1, secretion by stromal cells was higher compared to epithelial cells. In contrast, secretion of TGF-ß2 was higher in endometriotic stromal and endometriotic epithelial cells compared to normal endometrial cells. Treatment of endometrial and endometriotic stromal and epithelial cells with TGF-ß1 or TGF-ß2 increased Smad-dependent secretion of plasminogen activator inhibitor-1 (PAI-1) dramatically in all three cell lines. Of note, endometriotic cells secreted clearly higher levels of PAI-1 compared to endometrial cells. Whereas a TBR1 kinase inhibitor completely blocked the TGF-ß1 or TGF-ß2-induced PAI-1 secretion, an ERK1/2 inhibitor only partially reduced PAI-1 secretion. This inhibition was not dependent on epidermal growth factor receptor (EGFR) activation by phosphorylation but on kinase activity of the TBR1. Finally, treatment of endometrial and endometriotic cell lines with recombinant PAI-1 showed reduced cell adhesion, especially of the endometrial cells. In summary, our results demonstrate that both Smad-dependent and TBR1-dependent ERK1/2 pathways are necessary for TGF-ß-dependent high level secretion of PAI-1, which might increase cellular deadhesion.
Keywords: PAI-1; ERK; SMAD; TGF-betas; endometriosis; ddc:610